A note on units of finite local rings in an ascending chain - Andrade, Antonio Aparecido de [UNESP]; Shah, Tariq (My University, 2012)
In this paper we present matrices over unitary finite commutative local rings connected through an ascending chain of containments, whose elements are units of the corresponding rings in the chain such that the McCoy ranks are the largest ones.
Keywords: Galois ring; Galois field; BCH code; McCoy rank